Accommodating volume change and imparting thermal conductivity by encapsulation of phase change materials in carbon nanoparticles. Issue 6 (24th January 2018) - Advincula, P. A.; de Leon, A. C.; Rodier, B. J.; Kwon, J.; Advincula, R. C.; Pentzer, E. B.
Abstract : A Pickering-type emulsion is used as a template to encapsulate the phase change material stearic acid (SA) using graphene oxide nanosheets stitched together. Abstract : A Pickering-type emulsion is used as a template to encapsulate the phase change material stearic acid (SA) using graphene oxide nanosheets stitched together. GO-coated SA particles are solid at room temperature and can be used for latent heat storage during the phase change of the SA core. The carbon shell prevents leakage of SA during phase transition from solid to liquid, and also significantly improves the thermal conductivity. Additionally, integrity of the GO/PCM particles is maintained upon heating and cooling, even when the particles were composed of up to 85% PCM, maximizing the energy storage capabilities of the material. The "stitched" graphene oxide shells encapsulate, contain, and improve thermal conductivity of PCMs, and thus provide a new materials construct for thermal energy management and storage.